Content Marketing Strategy and Brand Image on Purchase Intention of Emina Products - Cindy Naomi Tampubolon; Tresya Lamtioria Bagariang; Yovika S.Simatupang (Publikasi Inspirasi Indonesia, 2026)
This study aims to analyze the influence of content marketing strategies and brand image on consumers’ purchase intention toward Emina cosmetic products. The research is motivated by the rapid growth of the Indonesian cosmetic industry and the increasing role of social media in shaping young consumers’ behavior. A quantitative research method was employed by distributing online questionnaires to 100 respondents aged 13–22 years who are Emina product users. The collected data were analyzed to measure the relationship between content marketing strategy, brand image, and purchase intention variables. The findings reveal that content marketing strategies and brand image significantly influence consumers’ purchase intention toward Emina products. Attractive, informative, and trend-relevant digital content effectively strengthens Emina’s “fun, young, and friendly” brand image. Social media platforms such as TikTok, Instagram, and YouTube play a vital role in building emotional connections between the brand and its consumers. Emina’s digital marketing strategy has proven effective in increasing brand awareness, shaping positive perceptions, and encouraging purchase intentions among teenagers and young adults. Therefore, this study emphasizes the importance of digital content marketing strategies and strong brand image development in addressing consumer behavior dynamics in the digital era. The findings are expected to serve as a reference for other local cosmetic companies in designing effective and sustainable marketing strategies.